THE EFFECT OF LEGAL COMPLIANCE ON THE FINANCIAL PERFORMANCE OF MSMES IN INDONESIA - Hidayat, Muhammad; White, Alan Robert; Supeno, Bambang (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
This study examines the influence of legal compliance on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a particular focus on financial stability, profitability, and competitiveness. Employing a descriptive-analytical design with a conceptual approach, this research synthesizes legal and financial theories through an extensive review of secondary data, including academic literature, regulatory frameworks, and governance studies. Legal compliance is operationalized across four key dimensions: business licensing, taxation, employment, and consumer protection. The findings indicate that legal compliance plays a strategic role in enhancing financial stability by reducing regulatory risks, minimizing unexpected costs, and improving cash flow management. Furthermore, compliance contributes to profitability through cost efficiency and improved access to financing with more competitive capital costs. In terms of competitiveness, legally compliant MSMEs demonstrate stronger reputational capital, greater market access, and higher adaptability within digital and global markets. The study also highlights that compliance should not be perceived merely as a regulatory obligation but as a financial strategy that strengthens governance quality and long-term business sustainability. However, the effectiveness of compliance is contingent upon regulatory simplification and MSME capacity, including legal literacy and administrative readiness. This study contributes to the integration of business law and financial performance perspectives in the MSME context and offers policy-relevant insights for strengthening MSME resilience.